2011
DOI: 10.4293/108680811x13022985131336
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Reaction to Absorbable Endoloop, Nonabsorbable Titanium Staples, and Polymer Hem-o-lok Clip After Laparoscopic Appendectomy

Abstract: The mildest inflammatory changes postoperatively were found in the staple group followed by those in the Hem-O-Lok group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…It has been shown to be as safe as other methods (15)(16)(17)(18). Delibegoviç et al (19) evaluated the effects of Endoloop, stapler and polymer clip applications on foreign body reaction and inflammation in an experimental study on rats, and reported that polymer clips were superior to other methods. The downside of clip use is its not being safe in case of intense inflammation where the diameter of appendix base is wide.…”
Section: Clipsmentioning
confidence: 99%
“…It has been shown to be as safe as other methods (15)(16)(17)(18). Delibegoviç et al (19) evaluated the effects of Endoloop, stapler and polymer clip applications on foreign body reaction and inflammation in an experimental study on rats, and reported that polymer clips were superior to other methods. The downside of clip use is its not being safe in case of intense inflammation where the diameter of appendix base is wide.…”
Section: Clipsmentioning
confidence: 99%
“…Polymer clips are reported to induce minimal soft tissue inflammation. 17 In our cohort we did not encounter any symptomatic foreign body reaction. The polymer clips are applied with long appliers through the 6mm working channel of the straight 10 mm 0 degree Storz telescope.…”
Section: Discussionmentioning
confidence: 70%
“…[15] The results of the study revealed both materials had acceptable tissue foreign body reaction and tissue reaction degree of the polymeric clips were slightly less than endo-loops. Moreover, the use of polymeric clips has been found to be safe and effective by the study of Hanssen et al with a special emphasize on cost effectiveness.…”
Section: Discussionmentioning
confidence: 79%